Lung–Kidney Interactions: Impact for Systemic Disease - Simatupang, Elvando Tunggul Mauliate; Wijaya, Dewi; Sembiring, Ligat Pribadi (Indonesian Society of Respirology (ISR), 2026)
Lung–kidney interaction is increasingly recognized as an important determinant of prognosis in systemic and critical illnesses. This is physiologically based and often occurs in daily medical practice. Evidence shows that dysfunction in one organ may trigger or worsen injury in the other, making this relationship relevant in clinical assessment and therapeutic decision-making. Understanding this bidirectional interaction is essential, as it influences disease severity, treatment response, and mortality. Direct or indirect, lung–kidney interactions are frequently observed in clinical practice. Hypercapnia, hypoxemia, and systemic inflammatory response are among many factors that can induce renal involvement in lung disease. Between lung complications and kidney function abnormalities, there is a correlation, such as pulmonary edema, pleural effusion, chronic kidney disease and acute kidney injury. The patients of acute kidney injury and chronic kidney disease may be more susceptible to lung issues due to several internal risk factors, including uremia, metabolic acidosis, electrolyte imbalances, and volume overload or increased fluid volume. Other external risk factors that also contribute to lung issues include systemic inflammation and oxidative stress. Occupational and environmental exposures may also contribute to lung disease, and indirectly accelerate renal function decline. Despite clinical relevance, lung–kidney interactions remain underrecognized in autoimmune diseases.